2019
DOI: 10.1186/s12938-019-0647-0
|View full text |Cite
|
Sign up to set email alerts
|

Processing of collagen based biomaterials and the resulting materials properties

Abstract: Collagen, the most abundant extracellular matrix protein in animal kingdom belongs to a family of fibrous proteins, which transfer load in tissues and which provide a highly biocompatible environment for cells. This high biocompatibility makes collagen a perfect biomaterial for implantable medical products and scaffolds for in vitro testing systems. To manufacture collagen based solutions, porous sponges, membranes and threads for surgical and dental purposes or cell culture matrices, collagen rich tissues as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
317
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 382 publications
(323 citation statements)
references
References 474 publications
(493 reference statements)
3
317
0
3
Order By: Relevance
“…This process includes several washing steps with different pH solutions to obtain neutralization and deantigenisation. At the end of the process a lyophilization and sterilization procedure is applied [42].…”
Section: Native Vs Cross-linked Collagenmentioning
confidence: 99%
See 3 more Smart Citations
“…This process includes several washing steps with different pH solutions to obtain neutralization and deantigenisation. At the end of the process a lyophilization and sterilization procedure is applied [42].…”
Section: Native Vs Cross-linked Collagenmentioning
confidence: 99%
“…Natural membranes made of collagen have the major handicap of rapid in vivo degradation failing to provide the structural integrity necessary for the entire process of bone regeneration [42]. The benefits of a cross-linked collagen membrane results in a barrier of increased area and thickness, compared with the application of a single layer collagen membrane.…”
Section: Native Vs Cross-linked Collagenmentioning
confidence: 99%
See 2 more Smart Citations
“…Further to this, indirect methods were used such as coating a TPP fabricated acrylate based scaffold with collagen [290], or loading collagen into a ceramic scaffold followed by gel casting [291]. A thorough review of using collagen as a biomaterial for cell culturing can be found here [292] and more specifically for collagen based bioinks, here [293].…”
Section: Process and Materialsmentioning
confidence: 99%